Beauty Body (Body Composition) among Fat Loss Program Participants A Case Study Longitudinal Primary Study - Dewi Atika Putri; Dwi Ratna Sari Handayani; Hafna Rosyita; Imam Waluyo; Muhamad Arsyad Subu; Koniasari Koniasari (Jurnal Health Sains, 2023)
Overweight and obesity can be risk factors for various diseases. The increasing prevalence of overweight and obesity is a public health problem and a challenge that needs to be addressed urgently. The purpose of this study is to periodically monitor body beauty (body composition) in clients running a fat loss program package. This type of research is a case study with a longitudinal design. The subjects in this study were clients who followed the fat loss program of 4 people who followed the program in June 2023 as determined by all subjects who followed the program in June 2023. Test instruments using meters and a Bioelectrical Impedance Analyzer (BIA-Omron) Data analysis using descriptive analysis of changes in body beauty indicators ( body composition ) The results show that: the fat loss program gives a decreased change in fat percentage before and after the program also reduces weight as well as increases muscle percentage thus giving a more proportional beautiful body appearance  Based on the results, it can be concluded that the fat loss program descriptively gives good results for the improvement of body composition and fat percentage and weight loss.